What influences nurses' decisions to work in rural and remote settings? A systematic review and meta-synthesis of qualitative research - Seonaid MacKay; Annetta Smith; Richard Kyle; Michelle Beattie (James Cook University, 2021)
Introduction: Due to global nursing shortages, recruitment and retention of nurses is a major international concern, exacerbated in rural and remote areas. Existing research reveals that individual factors influence healthcare professionals' decision making to work in rural and remote settings. However, existing evidence does not fully consider the multiple influences that may impact nurses' decisions to remain or leave rural and remote areas. This limits the effectiveness of recruitment and retention strategies. The objectives of this study were to explore the influences on nurses' decisions to work in rural and remote healthcare settings, using a systematic review and thematic meta-synthesis of qualitative studies. Methods: Databases Medline, Journals@OVID Full text, PsycInfo and specialist journals were searched from January 1990 to January 2020. Inclusion criteria were applied to all records by two independent reviewers. The Critical Appraisal Skills Programme checklist for qualitative studies was used for independent quality critique by two reviewers. Thematic synthesis was conducted using a three step process: (1) the results sections of each article were extracted and inductively coded line by line; (2) master themes and subthemes were organised into tables; (3) relationships between the themes were identified and examined to develop an overarching analytical framework. Results: A total of 121 articles were screened and 40 were included for data extraction and thematic synthesis. Thematic analysis identified three interrelated dimensions that influenced nurses' retention and migration decision-making, namely 'person/al', 'profession/al' and 'place' with 18 inter-related domains. The 'person/al' dimension contained five domains: a sense of belonging/connectedness, knowledge of rural culture, blurring of personal and professional lives, anonymity and job satisfaction/stress. The 'profession/al' dimension contained eight domains: expert generalist, advanced nurse practitioner, professional isolation, mentorship, education, autonomy and empowerment, role conflict, and recruitment and retention. The 'place' dimension identified five domains: terrain and weather, fewer resources, geographical isolation, safety and rural culture. The data informed the development of the MacKay's 3P (person/al, profession/al and place) model to capture the complex phenomenon of the influences on nurses' decision making to work in rural and remote settings. Conclusion: Multiple dimensions and domains influence nurses' decision making to work in rural and remote settings. MacKay's 3P model provides a theoretical framework to explore the complex interplay between the person/al, profession/al and place-related dimensions of rural nursing. These findings can inform the development of future recruitment and retention initiatives.